(untitled) ("Conference on Universal Science Research 2023", 2023)
The main general educational standard for foreign language is quality in foreign language learning sets tasks to achieve new goals, in particular: its components - speech, development of linguistic, socio-cultural, foreign language communicative compensatory and educational and cognitive. It is known that the communicative process of learning building, first of all, modeling the situation as a communication unit and its activity. This article provides information about Usage of grammatical structures in communication